Towards understanding clinical campylobacter infection and its transmission: time for a different approach?. Issue 2 (3rd April 2017) - Casey, E.; Fitzgerald, E.; Lucey, B.
Abstract: Campylobacter spp. are among the most commonly diagnosed causes of human infection. Methods for detection of the 29 campylobacter species have mainly focused on cultivation of the thermophilic species. More than 99% of clinical campylobacter isolates notified in the UK in the recent past have been from faecal samples and associated with gastroenteritis. Campylobacter enteritis notifications in temperate zones show a seasonal increase during the summer months with a sharp decrease in the winter months, a pattern which remains incompletely understood. The striking seasonality in the expression of many human genes, some concerned with inflammation and immunity, suggests a need for further study of the host regarding the temporal distribution of many human infections, including campylobacteriosis. A tendency for campylobacter to enter a non-cultivable state under adverse conditions effects a reduction in the number of isolations. A Polymerase Chain Reaction (PCR)-based screening approach for the presence of the Campylobacter genus and followed by speciation has provided some insight into the limitations of cultivation for campylobacter, also allowing the discovery of new species. The increased sensitivity of the PCR-based approach over culture-based methods may make it difficult for the laboratory to differentiate asymptomatic campylobacter carriage from clinical campylobacter infection in non-sterile body sites. Campylobacter infection depends on a combination of host factors, and on acquisition of a suitably virulent strain with a tropism for human epithelium. The possibility of persistence of campylobacter in a viable but non-culturable latent form in the human body may also require further investigation. The scope of this review includes a discussion of current methods for diagnosing acute campylobacter infection and for detecting campylobacter in water and foodstuffs. The review also questions the prevailing view that poultry is the most common source of campylobacteriosis.